MODEL PENGEMBANGAN UMKM EKONOMI KREATIF BERBASIS ISLAMIC ENTREPRENEURSHIP DI KOTA CIREBON - Hikam Muhtadi Zuhdi; Wartoyo; Sri Rokhlinasari (CV. ADIBA AISHA AMIRA, 2025)
Creative economy is a new economic concept that combines information and creativity by relying on ideas, concepts and knowledge from human resources as factors of production. In economic studies, there are four factors of production: natural resources, human resources, capital, and orientation or core management or the heart of the creative economy. However, there is still no model that can bridge the needs of economic innovation with a commitment to Islamic principles such as honesty, trustworthiness, social responsibility, and the blessings of business. Research objectives: (1) To identify, analyse, and examine the characteristics of MSMEs in Cirebon City from an Islamic entrepreneurship perspective. (2) To identify, analyse, and examine the strategies of the Cirebon City Government in developing a creative economy based on Islamic entrepreneurship in MSMEs in Cirebon City. (3) To formulate a model for developing a creative economy based on Islamic entrepreneurship in MSMEs in Cirebon City. This research uses a qualitative descriptive approach, which will describe a phenomenon that is currently occurring, focusing on issues that arise during the research. The results of this study are: (1) MSMEs in Cirebon City have essentially internalised the values of Islamic Entrepreneurship in practice, although they have not formally identified themselves as Islamic entrepreneurs, (2) strategies for developing MSMEs, such as training, exhibition facilitation, and capital assistance, by integrating Islamic values.(3) The model proposed in this study is the Islamic Quadruple Helix Model, which integrates four main pillars, namely the government, academia, business actors/SMEs, and the Islamic community.